Operacní lécba zlomenin diafýzy humeru - Smejkal, K; Dedek, T; Lochman, P; Zahradnícek, J; Zvák, I; Trlica, J (Rozhledy v chirurgii, 2008)
INTRODUCTION: Nowadays the humeral shaft fractures represent about 4% of all fractures. Most of them can be treated conservatively. In this type of treatment the cooperation of the patient is necessary, treatment is long lasting and needs the extremity to be immobilized. That's why still more fractures are indicated for the operation treatment, which enables an early rehabilitation and selfcare of the patient. AIM: The aim of our work was to assess the functional and clinical results in patients after the operation of the humeral shaft fractures treated by closed reposition and intramedullary fixation or by open reposition and plate osteosynthesis (ORIF). DESIGN: Retrospective descriptive study--case serie MATERIAL AND METHODS: In our department within the years 2001-2006 we operated on 101 patients with humeral shaft fractures. 65 patients came to be checked, the follow up rate--65%. Fractures were classified according AO: A--50%, B--29%, C--21%. The ORIF was used in 18 patients, closed reduction and locked intramedullary nail in 21 patients, and closed reduction and K-wires bundle (Hackethal) in 26 patients. RESULTS: The resulting conditions we evaluated by Constant-Murley and Liverpool elbow scoring system. The mean value reached 86/8.9. In 82% of patients we have reached good to excellent results. Complications were noted in 34 CONCLUSION: In spite of limited number of patients in our study the results of ours generally are not in contradiction to the current literature data. The best results were achieved by ORIF. On the contrary, the worst outcomes with greatest number of complications were in Hackethal group.
Keywords: senioři; senioři nad 80 let; mladiství; Radiography; Middle Aged; mužské pohlaví; Adult; mladý dospělý; kostní destičky; Aged, 80 and over; Young Adult; ženské pohlaví; fraktury humeru; radiografie; Humans; lidé středního věku; Bone Plates; Fracture Fixation, Intramedullary; dospělí; Female; Aged; Adolescent; intramedulární fixace fraktury; Humeral Fractures; lidé; Male